2018
DOI: 10.1111/jcmm.13899
|View full text |Cite
|
Sign up to set email alerts
|

The red wine component ellagic acid induces autophagy and exhibits anti‐lung cancer activity in vitro and in vivo

Abstract: Red wine consists of a large amount of compounds such as resveratrol, which exhibits chemopreventive and therapeutic effects against several types of cancers by targeting cancer driver molecules. In this study, we tested the anti‐lung cancer activity of 11 red wine components and reported that a natural polyphenol compound ellagic acid (EA) inhibited lung cancer cell proliferation at an efficacy approximately equal to that of resveratrol. EA markedly increased the expression of the autophagosomal marker LC3‐II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…14 The anticarcinogenic effect of EA has been shown in some types of tumors, including prostate cancer, lung cancer, osteosarcoma, breast cancer, and so forth. [15][16][17][18] Consistent with previous studies, EA also showed good antitumor activity in ESCC. We found that EA inhibited ESCC cell survival by inducing cell apoptosis.…”
Section: Discussionsupporting
confidence: 89%
“…14 The anticarcinogenic effect of EA has been shown in some types of tumors, including prostate cancer, lung cancer, osteosarcoma, breast cancer, and so forth. [15][16][17][18] Consistent with previous studies, EA also showed good antitumor activity in ESCC. We found that EA inhibited ESCC cell survival by inducing cell apoptosis.…”
Section: Discussionsupporting
confidence: 89%
“…Ellagic acid has shown multiple protective effects during brotic diseases such as liver brosis, pancreatic brosis and cardiac brosis [23][24][25]. Ellagic acid promoted apoptosis and autophagy, suppressed Wnt/β-catenin and mTOR pathways in tumor cells [26][27][28]. In addition, previous studies have reported that Ellagic acid could attenuate BLM-induced pulmonary brosis in rats [29,30], but the therapeutic effect of BLM-induced pulmonary brosis in mice and its mechanism are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxybenzoic acid derivatives have been studied for their role in modulating autophagy and cancer cell growth. Duan et al reported that ellagic acid (10-50 µM) activated autophagy, but not apoptosis, in lung cancer cells (HOP62 and H1975), and in tumor-bearing mice (40 mg/kg, i.p., every 2 days, for 22 days), as demonstrated by the formation of LC3-positive autophagosomes, the increase in LC3 II, ATG5 and the reduced levels of p62 [238]. Similarly, ellagic acid (36.6 µM) inhibited cell growth and the invasiveness of ovarian cancer SKOV-3 cells and stimulated apoptosis by activating cytotoxic autophagy, as indicated by the increase in the levels of Beclin 1, ATG5, LC3I/II and decrease in p62 [239].…”
Section: Phenolic Acidsmentioning
confidence: 95%
“…Similarly, ellagic acid (36.6 µM) inhibited cell growth and the invasiveness of ovarian cancer SKOV-3 cells and stimulated apoptosis by activating cytotoxic autophagy, as indicated by the increase in the levels of Beclin 1, ATG5, LC3I/II and decrease in p62 [239]. In addition, it was shown that ellagic acid activated autophagy through the downregulation of mTORC1 and Akt, and the activation of AMPK [238,239]. The activation of apoptotic and autophagic cell death was also reported for punicalagin, an ellagitannin isolated from the fruit of Punica granatum L. trees.…”
Section: Phenolic Acidsmentioning
confidence: 96%